Political Communications, State, and Institutionalization of Democracy - Evie Ariadne Shinta Dewi (MediaTor (Jurnal Komunikasi), 2017)
The main thesis of this paper is reveals how the process of political communication should take place in order to achieve the idealization of democracy in accordance with the objectives of post-collapse reform of the authoritarian new order era. After nearly 18 years of reformation, substantial issues and basic problems still seem to burden the government. On the other hand, political democratization process seems to be influenced by the old pattern. This paper elaborates how the role of political communication in the process of democratization has been going on. The data obtained through documentation studies from various sources. The results of the study indicate that a state that should be positioned as the main actor in the process of political communication is often overlooked because of the large number of noise that caused by the main message of the state which is not well conveyed. As the result, the institutionalization of democratic values is still not the main commitment of the political parties. In the future, this country needs a strategy that puts the state both as a communicator and a communicant, so that the consolidation of democracy can be realized soon.